Potential Suitability and Carrying Capacity of the Mangrove Ecosystem for Ecotourism in Coastal Pejarakan Village - purnama, Fajar adi; Yulianto, Gatot; Kurnia, Rahmat (Agrikan Jurnal Agribisnis Perikanan, 2023)
Analysis of suitability and carrying capacity are two fundamental aspects in assessing the suitability of an area for a particular designation concerning sustainability aspects. Pejarakan Village, one of the villages on the north coast of Buleleng Regency, Bali Province, has a natural potential to be developed for marine tourism activities. However, mangrove ecosystem management in general has not been optimally implemented to become an added economic value for the local community. Therefore, to realize the sustainable utilization of coastal areas, especially mangroves in Pejarakan Village to become a new Tourism Attraction Object (ODTW), a regional carrying capacity study (DDK) and a tourism suitability analysis (IKW) were carried out. This study aims to analyze the tourism suitability index based on the potential of mangrove resources and calculate the carrying capacity of an area based on the number of people that can be accommodated in an area at a certain time without causing disturbance to nature or humans. The research uses an in situ scheme using the Spot Check Method and purposive sampling of mangrove ecosystems to analyze the tourism suitability index and the area’s carrying capacity. This research was conducted from October to November 2022 in the mangrove area of Pejarakan Village. Based on the study’s results, a suitable tourism suitability index was obtained in the northern part of the area (area 2), and then the potential length of the mangrove track was approximately 700 meters and could accommodate 112 people per day.